Paleomicrobiology Past Human Infections - Raoult, Didier; Drancourt, Michel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
"Paleomicrobiology – Past Human Infections" features the methods and main achievements in this emerging field of research at the intersection of microbiology and evolution, history and anthropology. New molecular approaches have already provided exciting results, such as confirmation of a single biotype of Yersinia pestis as the causative agent of historical plague pandemics, and the closer proximity of Mycobacterium tuberculosis from ancient skeletons to modern strains than to Mycobacterium bovis, shedding new light on the evolution of major human pathogens and pathogen–population relationships. Firm microbiological diagnoses also provide historians and anthropologists with new data on which to base evaluation of past epidemics.
The Techniques and Methods -- Great Plagues of the Past and Remaining Questions -- Identification and Interpretation of Historical Cemeteries Linked to Epidemics -- Archaeological Proof of an Abrupt Mortality Crisis: Simultaneous Deposit of Cadavers, Simultaneous Deaths? -- Molecular Detection of Past Pathogens -- Histologic Detection of Past Pathogens -- Ancient Microorganisms Bacteria -- Palaeomicrobiology of Tuberculosis -- Past Leprae -- Archaeology of Human Pathogens: Palaeopathological Appraisal of Palaeoepidemiology -- Past Plague -- Typhoid Fever Epidemic in Ancient Athens -- Dental Pulp as a Tool for the Retrospective Diagnosis of Infectious Diseases -- History of Influenza Pandemics -- Human lice: Pediculus and Pthirus.
Keywords: Microbiology; Medical microbiology; Anthropology; Archaeology; Microbiology; Medical Microbiology; Anthropology; Archaeology